Three-dimensional DSMC simulation of thermal Knudsen force in micro gas actuator for mass analysis of gas mixture. (August 2020) - Li, Yicheng; Abazari, A.M.; Barzegar Gerdroodbary, M.; Dinh Manh, Tran; Dang Nam, Nguyen; Valipour, P.; Moradi, R.; Babazadeh, Houman
Highlights: 3D computational studies are done to evaluate the detection of the micro sensor. The impact of the geometrical parameters on the precision of the micro sensor is investigated. The influence of the temperature gradient on the detection is also examined. Flow structure and temperature distribution within the sensor is investigated. The sensor is calibrated for the measurement of the CO2 in the mixture. Abstract: High precision detection and measurement of the components of a gas mixture are highly significant in chemical industries. In the textile industry, CO2 is widely used to dye the textile material without water called Supercritical Fluid Dyeing Technology. In this study, a computational technique is applied to investigate the ability of an innovative MEMS gas actuator (MIKRA) for the sensation of the specific component in the gas mixture. This work also investigated various mixtures of gases and various relative concentrations of CO2 to N2 . In this actuator, the temperature dissimilarity of two arms at rarefied conditions produces a Knudsen force. Due to the micro size of this sensor, this actuator is highly significant for the inaccessible detection domain. This work tries to reveal the main mechanism for this sensor to increase the precision of the detection. The flow patterns of a mixture gas within this micro gas sensor are examined by Direct Simulation Monte Carlo (DSMC) method since the domain of this micro gas is non-equilibrium. According to the obtained results, a three-dimensional model presents more reliable results and the effect of a gap for the three-dimensional model demonstrates the impact of this parameter on the effective Knudsen force.